Systemic immunoregulatory and proteogenomic effects of tacrolimus to sirolimus conversion in liver transplant recipients1. Issue 1 (17th July 2012) - Levitsky, Josh; Mathew, James M.; Abecassis, Michael; Tambur, Anat; Leventhal, Joseph; Chandrasekaran, Dhivya; Herrera, Nancy; Al‐Saden, Patrice; Gallon, Lorenzo; Abdul‐Nabi, Anmaar; Yang, Guang‐Yu; Kurian, Sunil M.; et al.
Abstract Immunosuppression (IS) withdrawal from calcineurin inhibitors is only possible in ∼20% of liver transplant recipients. However, mammalian target of rapamycin inhibitors (e.g., sirolimus; SRL) appear to be more immunoregulatory and might promote a tolerant state for withdrawal. Our aim was to determine whether systemic (i.e., blood, marrow, and allograft) signatures of immunoregulation are promoted by conversion from tacrolimus (TAC) to SRL. We therefore performed the following serial assays before and after SRL conversion in liver transplant recipients to test for enhanced markers of immunoregulation: (1) flow‐cytometry immunophenotyping of peripheral blood mononuclear cells (PBMCs) and bone marrow aspirates for regulatory T cells (Tregs) (e.g., CD4+CD25+++FOXP3+) and regulatory dendritic cells (DCregs) (immunoglobulin‐like transcript 3+/4+); (2) liver biopsy immunohistochemical staining (e.g., FOXP3:CD3 and CD4:CD8 ratios) and immunophenotyping of biopsy‐derived Tregs after growth in culture; (3) effects of pre‐ versus postconversion sera on Treg generation in mixed lymphocyte reactions; (4) peripheral blood nonspecific CD4 responses; and (5) peripheral blood gene transcripts and proteomic profiles. We successfully converted 20 nonimmune, nonviremic recipients (age, 57.2 ± 8.0; 3.5 ± 2.1 years post–liver transplantation) from TAC to SRL for renal dysfunction. Our results demonstrated significant increases in Tregs in PBMCs and marrow and DCregs in PBMCs (P < 0.01) after conversion. In biopsy staining, FOXP3:CD3 and CD4:CD8 ratios were significantly higher after conversion and a number of biopsy cultures developed new or higher FOXP3+ cell growth. Nonspecific CD4 responses did not change. Both pre‐ and postconversion sera inhibited mixed lymphocyte reactions, although only TAC sera suppressed Treg generation. Finally, 289 novel genes and 22 proteins, several important in immunoregulatory pathways, were expressed after conversion. Conclusions: TAC to SRL conversion increases systemic Tregs, DCregs, and immunoregulatory proteogenomic signatures in liver transplant recipients and may therefore facilitate IS minimization or withdrawal. (HEPATOLOGY 2013)